Predictor of neonatal morbidity in birth asphyxia - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2015)
Hypoxic ischaemic brain damage is a major cause of neonatal mortality and morbidity. Similar degrees of insult may completely spare one child and devastate another, so very sensitive prognostic parameters are needed. Conventional predictors like fetal heart rate patterns, Apgar scores, need for resuscitation and umbilical arterial blood gas analysis show variable predictive values of outcome in neonates with asphyxia.